324 LIPOPROTEIN LIPASE-MEDIATED FATTY ACID METABOLISM IN THE SPLANCHNIC BED. (1st January 2006) - Nelson, R. H.; Basu, R.; Johnson, C. M.; Roesner, J. C.; Rizza, R. A.; Miles, J. M.
Abstract : It is generally believed that the role of lipoprotein lipase (LPL), which resides on the capillary endothelium, is to mediate transport and storage of lipoprotein triglyceride fatty acids locally in tissues. However, LPL could also contribute to circulating plasma free fatty acids (FFA) if, instead of in situ transport and storage, there were "spillover" of LPL-generated fatty acids into blood. We have previously reported ≈14% fractional spillover in the forearm of postabsorptive subjects. The present study was undertaken to determine the efficiency of triglyceride storage in the splanchnic bed and the contribution of the splanchnic bed to whole-body triglyceride disposal. We studied postabsorptive overweight and obese, non-diabetic adults ( N = 6) after an overnight fast. Infusions of tracer amounts of [1-1 4 C]oleate and a lipid emulsion labeled with [9, 10-3H]triolein were started, allowing 2 hours to establish isotope equilibrium. Blood sampling catheters were placed in the femoral artery (A) and hepatic vein (HV); paired A and HV samples were then taken every 10 min for 40 min. Systemic and splanchnic rate of appearance (Ra ) of [ 3 H]oleate, resulting from the action of LPL on the infused triglyceride tracer, was quantified by a calculation in which [ 14 C]oleate is the tracer and [ 3 H]oleate is the tracee. Fractional spillover of LPL-generated fatty acids was calculated as the Ra of [ 3 H]oleate divided by the disappearance rate of the [ 3 H]triglyceride tracer, both for whole body and for the splanchnic bed. Indocyanine green was infused for determination of splanchnic blood flow. Plasma FFA concentrations were lower in HV than in A (533 ± 78 vs 805 ± 128 μmol/L, p < .005). Systemic oleate Ra was 3.6 ± 0.8 μmolkgμ1minμ1. Fractional extraction of radiolabeled oleate by the splanchnic bed was greater than that of radiolabeled triglyceride (34 ± 1% vs 11 ± 2%, p < .002). Splanchnic oleate and triglyceride uptake was 37 ± 7 and 25 ± 4% of systemic uptake, respectively. Systemic fractional spillover of LPL-generated fatty acids was 50 ± 7%, whereas splanchnic spillover was nearly 100%. These results indicate that in the postabsorptive state in obese subjects, LPL-mediated fat storage from triglyceride-rich lipoproteins (likely occurring in visceral fat) is inefficient and that splanchnic LPL may contribute substantially to plasma (especially portal venous) FFA concentrations. This contrasts markedly with the relatively low spillover previously observed in the forearm. Whether LPL-mediated fat storage in the splanchnic bed is more efficient in lean subjects and more efficient in the postprandial state will require further investigation.